1994
DOI: 10.1183/09031936.94.07122192
|View full text |Cite
|
Sign up to set email alerts
|

Slow and fast changes in transmural pulmonary artery pressure in obstructive sleep apnoea

Abstract: S Sl lo ow w a an nd d f fa as st t c ch ha an ng ge es s i in n t tr ra an ns sm mu ur ra al l p pu ul lm mo on na ar ry y a ar rt te er ry y p pr re es ss su ur re e i in n o ob bs st tr ru uc ct ti iv ve e s sl le ee ep p a ap pn no oe ea a Transmural systolic pulmonary artery pressure (Ppa,STM), oxyhaemoglobin saturation (SaO 2 ) and oesophageal pressure were analysed in two samples of consecutive obstructive apnoeas in each of four patients.In the first samples (samples A; probably recorded during non-rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 26 publications
(30 reference statements)
2
20
0
Order By: Relevance
“…Our data strongly support the fact that both oxygen desaturation and intrathoracic pressure swings account for the changes in Ppa,tm within an apnoea. This is consistent with the data from MARRONE et al [11], who observed rapid changes which reflect intrathoracic pressure variations and slower changes likely to be caused by Sa,O 2 chan-ges. In contrast to our study, they investigated firstly Ppa,tm beat-by-beat, in reference to the immediately preceding end-diastole Poes and, secondly, Ppa,tm changes in reference to Sa,O 2 changes within an apnoea.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our data strongly support the fact that both oxygen desaturation and intrathoracic pressure swings account for the changes in Ppa,tm within an apnoea. This is consistent with the data from MARRONE et al [11], who observed rapid changes which reflect intrathoracic pressure variations and slower changes likely to be caused by Sa,O 2 chan-ges. In contrast to our study, they investigated firstly Ppa,tm beat-by-beat, in reference to the immediately preceding end-diastole Poes and, secondly, Ppa,tm changes in reference to Sa,O 2 changes within an apnoea.…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, several studies have indicated an association between changes in oxygen saturation and changes in pulmonary artery pressure during an obstructive apnoea [4,9,10]. MARRONE et al [11] showed that hypoxia is a major determinant of the slow changes in the transmural pulmonary artery pressure over the whole course of an apnoea. In addition, they found rapid changes in the Ppa,tm that was synchronous with intrathoracic pressure changes breathby-breath.…”
mentioning
confidence: 99%
“…It has been demonstrated experimentally [3][4][5]12] that pulmonary vascular responsiveness depends on the intensity, the duration and the repetition of the hypoxic stimulus applied. MARRONE et al [17] found that transmural systolic Ppa progressively increased during repetitive apnoeas in four OSAS patients only when the falls in Sa,O 2 became greater and in REM sleep. In our analysis, we first included values during NREM and REM sleep so that changes in Ppa would reflect the time course during the night.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with OSA, large swings of intrathoracic pressure during apnoea greatly affect intravascular PAP. To assess HPV during apnoeic episodes, true transmural PAP has to be measured [71]. HPV is resolved at the resumption of breathing [72].…”
Section: Intermittent Hypoxia In Copd Patients On Long-term Oxygen Trmentioning
confidence: 99%